Pengaruh dimensi attachment avoidance dan anxiety terhadap kualitas hubungan berpacaran dewasa muda - Angela, Irene; Ariela, Jessica (Jurnal Psikologi Udayana; Vol 8 No 1 (2021), 2021)
Dating relationship is a crucial part of the human life particularly for the young adults that it can affect the mental health of a person. Hence, the quality of dating relationship should be thoroughly considered because bad dating relationship could contribute negatively to a person’s life, to the person’s relationship with other people in the future and further to the next phase of dating relationship (marriage). Prior researches show that attachment is the preeminent indicators of the quality of relationship. Attachment is human desire to establish relationship based on shared affection with other individuals. Attachment also determines the direction and the basic understanding of individual toward that relationship. The objective of this research is to discern the dimension effect of attachment toward the quality of dating relationship for the young adults. Total participant of this research is 145 people. This research uses quantitative research method with measuring instrument of ‘The Experiences Close Relationship-Revised dan The Perceived Relationship Quality Component.’ The result of this research shows that there is dimension effect of attachment toward the quality of dating relationship by 44,8%. However, attachment avoidance give bigger impact towards relationship quality compare with attachment anxiety.